2004
DOI: 10.1183/09031936.04.00107004
|View full text |Cite
|
Sign up to set email alerts
|

Increased gastro-oesophageal reflux disease in patients with severe COPD

Abstract: The prevalence and clinical consequences of gastro-oesophageal reflux disease (GERD) in chronic obstructive pulmonary disease (COPD) are not well characterised.The present study prospectively studied 42 males with COPD (forced expiratory volume in one second % predicted: 35%, range 20-49) and 16 healthy volunteers of similar age without respiratory or gastro-oesophageal symptoms. The diagnosis of GERD was confirmed using oesophageal 24 h pH monitoring. In the current study group, reflux symptoms were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
2
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 29 publications
(36 reference statements)
5
126
2
10
Order By: Relevance
“…33 Another cross sectional study found that decreases in oesophageal pH corresponded with drops in oxygen saturation among six of 15 patients with GORD and COPD. 31 …”
Section: Connective Tissue Diseasementioning
confidence: 99%
“…33 Another cross sectional study found that decreases in oesophageal pH corresponded with drops in oxygen saturation among six of 15 patients with GORD and COPD. 31 …”
Section: Connective Tissue Diseasementioning
confidence: 99%
“…Although our sample of subjects was small, the use of esophageal pH monitoring takes into account the broader profile of gastroesophageal reflux in bronchiectasis or COPD, for which both symptomatic and asymptomatic reflux have been described. 3,5,6,[36][37][38] In this study, the absence of a relationship between a diagnosis of gastroesophageal reflux and EBC pepsin con- centrations is contrary to the lower EBC pH and higher pepsin concentrations in patients with COPD and symptomatic reflux. 21 This may reflect the small number of subjects in this study meeting the criteria for gastroesophageal reflux, a limitation when including subjects irrespective of reflux symptoms.…”
Section: Discussionmentioning
confidence: 40%
“…(11) Although, GERD is usually confined to the lower oesophagus in some individuals, it may be associated with pulmonary microaspiration of gastric contents. Possible mechanisms that may contribute to GERD in COPD originate from gastro-oesophageal dysfunction including altered pressure in the lower oesophageal sphincter (which normally protect against GERD) and changes in oesophageal motility.…”
Section: Prevalence Of Gerdmentioning
confidence: 99%